Validation of a three-dimensional finite element model of flex-pole impacts - Schindelwig, K.; Ellensohn, S.; Kaps, P.; Nachbauer, W. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2017)
Slalom skiers hit flex poles whereby an impulse is transferred from the skier to the flex pole. Each such impact leads to a speed reduction of the skier, which is clearly greater for relatively lighter skiers than it is for relatively heavier skiers. Additionally, there is an injury risk for the skier caused by the impact and the risk for breakage of the flex pole. For a detailed analysis of causes and consequences of this impact, three-dimensional finite element models were developed for flex poles and a pendulum impactor. The finite element models were validated by comparing data of experiments with the pendulum impactor and simulations. The comparisons included flex-pole motion, flex-pole speed, whiplash measure, pendulum impulse loss and cross-sectional deformed oval shapes. The differences of the comparisons were less than 3% for the first four parameters. The comparison of the cross-sectional deformed oval shapes` behavior agreed well. With the new validated finite element model, the influence of factors such as flex-pole diameter, wall thickness, length and material properties on the transferred impulse and the mechanical loadability of the flex pole can be systematically analyzed. With this knowledge, specifications for flex poles can be adapted to improve fairness at slalom races and reduce the injury risk and the danger of damaging the upright pole.